A Meta-Analysis of the Faking Resistance of Forced-Choice Personality Inventories - Martínez, Alexandra; Salgado, Jesús F. (Frontiers in Psychology, 2021)
This study presents a comprehensive meta-analysis on the faking resistance of forced-choice (FC) inventories. The results showed that (1) FC inventories show resistance to faking behavior; (2) the magnitude of faking is higher in experimental contexts than in real-life selection processes (δ =.46/.12 vs. δ = -.14/-.25), suggesting that the effects of faking may be, in part, a laboratory phenomenon; and (3) quasi-ipsative FC inventories are more resistant to faking than the other FC formats. Smaller effect sizes were found for conscientiousness when the quasi-ipsative format was used (δ = .49 vs. δ = 1.27 for ipsative formats). To conclude, the contributions and practical implications of these findings are discussed.